DIAGNOSTIC ACCURACY OF ULTRASOUND IN ACUTE APPENDICITIS IN COMPARISON WITH ALVARADO SCORE KEEPING HISTOPATHOLOGICAL CORRELATION AS GOLD STANDARD - Farooq, Ambreen; Zameer, Shahla; Khadim, Rehana (Pakistan Armed Forces Medical Journal, 2020)
Objective: To evaluate the diagnostic accuracy of ultrasound in acute appendicitis in comparison with Alvarado score keeping histopathological correlation as gold standard.Study Design: Comparative cross-sectional study. Place and Duration of Study: Departments of Radiology, Surgery and Pathology of PIMS Hospital, Islamabad, from Jan 2018 to Oct 2018.Methodology: Patients that were Alvarado positive or either ultrasound positive were included in the study followed by appendectomy. Removed appendix was sent for histopathological examination. The results were entered in structured proformas.Results: Out of 200 patients, 117 (58.5%) were male patients while 83 (41.55%) were females. Mean age of the patients was 22.6 ± 3.1 year with range 9 to 55 years. Mean Alvarado score of patients was found to be 9.1 with maximum score 10 and minimum score of 7. Among ultrasound findings, 192 (96%) patients had appendix with diameter >6mm. Ninety two (46%) patients had free fluid, 186 (93%) patients had peri-appendicular fat and 40(20.0%) patients had appendicolith. Sensitivity of ultrasonography was 80%, sensitivity of Alvarado was 94.1%. Specificity of ultrasound was 60%, specificity of Alvarado was 33.3%. Diagnostic accuracy of ultrasonography was 77.5%, Alvarado score was 85%. Conclusion: Alvarado score has higher sensitivity as compared to ultrasound, while ultrasound has a higher specificity. Neither tool is superior to the other. Both need to be used together to reduce the negative appendectomy rates.